"Future Library Unconference 2013" Athens, 9-10 december 2013 - Nastić, Olivera (Infotheca - Journal for Digital Humanities, 2024)
During the period from the 9th to the 10th of December 2013 the „Future Library Unconference 2013” was held in Athens. This kind of (un) conference was organized by the Future Library Organization, and the host was The Benaki Museum.